Teda MS22 (eHRAF World Cultures, 2011)
The documents in the Teda collection, all of them in English, cover a wide variety of cultural, historical and ecological information, circa 1930s to 1980s. The basic sources to consult are two documents translated from French and German to English for HRAF. One is the work of Jean Chapelle, a Colonel in the French army who, arriving at the inception of the final French occupation in early 1930s, worked among the Teda of Tibesti for twenty-five years. The other is by Andreas Kronenberg, a German-speaking professional anthropologist, who conducted fieldwork in the same area in 1953-1954. Together, these documents provide comprehensive information on Teda culture, history, environment, settlement pattern, clan system, material culture, and religious life. The remaining documents compliment these classic ethnographic accounts with additional information. One of these documents provides a general description of Teda culture and society based on fieldwork both in Tibesti and two other locations not covered by previous researchers. A second document is an ethnographic dictionary with covers numerous small but often unique bits of information on a wide range of topics. The remaining last document is a journal article discussing how the Teda came to conquer the Chadian State by establishing dominance in central government in the later 1970s and early 1980s